Developmental errors in reading of L1 speakers of English among selected Filipino children - Torrato, Janette B. (Animo Repository, 2004)
The study of the developmental errors in reading is a pioneer study among English speaking Filipino children. This study determines the English phonemes with highest frequency of errors among the Filipino children whose L1 is English and the factors that might have affected them to commit these errors. The final question is concerned with the correlation between the children's score in an English diagnostic test and their pronunciation errors in an oral reading test. The participants were 104 grade 2 students from one of the private schools of a predominantly upper-middle-socio-economic village in the South of Metro Manila. The procedures include text reading, recording and coding of data to assess the pronunciation errors committed by the children. A student profile was distributed for the parents to answer to determine the factors that might have affected them to commit errors. The final question concerning the relationship of their score in an English diagnostic test was correlated with their phonological errors. The results show that the phonemes with the highest frequency or errors are the th, ed, ph, sh, p, t, s, r, a, o, e, i, u, o and letter vowel combinations like oo, uie, eau, ea, ai, ua. The strong association of the linguistic environment which includes both home and school as well as the effect of other languages that might have affected them to commit these errors were recognized. The result of the correlation proves that there is a little or insignificant relationship between their score in an English diagnostic test and pronunciation errors in an oral reading test.